2009
DOI: 10.1093/ndt/gfp351
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute variation of dialysate calcium concentrations on arterial stiffness and aortic pressure waveform

Abstract: Background. Abnormal mineral metabolism in chronic kidney disease plays a critical role in vascular calcification and arterial stiffness. The impact of presently used dialysis calcium concentration (DCa) on arterial stiffness and aortic pressure waveform has never been studied. The aim of the present study is to evaluate, in haemodialysis (HD) patients, the impact of acute modification of DCa on arterial stiffness and central pulse wave profile (cPWP).Method. A randomized Latin square cross-over study was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 30 publications
1
43
0
4
Order By: Relevance
“…37 Other studies have reported that increased calcium in dialysate acutely worsens arterial compliance and minimizes intradialytic BP reduction. 38 At least in theory, high calcium dialysate may worsen the hemodynamic response to ultrafiltration dialysis in patients with intradialytic hypertension.…”
Section: Calciummentioning
confidence: 99%
“…37 Other studies have reported that increased calcium in dialysate acutely worsens arterial compliance and minimizes intradialytic BP reduction. 38 At least in theory, high calcium dialysate may worsen the hemodynamic response to ultrafiltration dialysis in patients with intradialytic hypertension.…”
Section: Calciummentioning
confidence: 99%
“…Since impaired mineral metabolism is a strong and independent predictor of mortality in hemodialysis [27] , the intermittently higher calcium phosphate product during the long interdialytic interval may worsen the outcomes in these patients. Furthermore, recent studies have shown that high dialysate calcium concentrations acutely raise BP and worsen arterial compliance during dialysis [28] . Prospective studies support that session-to-session variability in serum calcium and phosphate levels is a predictor of mortality in hemodialysis [29,30] .…”
Section: Calcium and Phosphatementioning
confidence: 99%
“…Some epidemiologic and cohort studies have implicated calcium loads from either the dialysate or from oral phosphate binders in the development of vascular calcifi cations, but this association has not been observed in all observational settings. 8,[10][11][12][13] In the general population, calcium supplementation is associated with reduced blood pressure and has been advocated by some as potentially reducing cardiovascular risk through a favorable effect on blood pressure. The results of two large studies, one of which is reviewed here (Pentti and colleagues), challenge conventional wisdom and provide evidence for potential harm with calcium supplementation in a healthy elderly population.…”
Section: Nephrology Literature Watchmentioning
confidence: 99%